Unimodality of Boolean and Monotone Stable Distributions - Hasebe Takahiro; Sakuma Noriyoshi (Demonstratio Mathematica, 2015)
We give a complete list of the Lebesgue-Jordan decomposition of Boolean and monotone stable distributions and a complete list of the mode of them. They are not always unimodal.